Ethnobotanical survey on medicinal plants traditionally used for treatment of intestinal parasitosis of animals and humans in Northern Benin - LAGNIKA, LATIFOU (My University, 2021)
Parasitic nematodes of the gastrointestinal (GI) tract remain a major threat to both human beings and livestock. The aim of this study was to document medicinal plants used in the management of intestinal parasitosis in the small ruminants and humans. Information relating to the different plants used in the treatment of human intestinal parasitosis and small ruminants was collected through an ethnobotanical survey carried out in the DONGA Department of Benin. On subjecting the traditional healers and small ruminant breeders to a questionnaire, it appears that intestinal parasitosis is manifested mainly by transit disorders (vomiting, abdominal pain, diarrhoea). Forty-four species belonging to twenty-two families were documented and used in the treatment of intestinal parasitosis. Fabaceae is the most represented family and species common to traditional human and veterinary medicine have been reported. Khaya senegalensis was the most cited species used in the treatment of intestinal parasitosis by traditional healers (9%) and small ruminant breeders (27%). A brief review of the literature provided summary of the medicinal plants used in the treatment of intestinal parasitosis. It also made it possible to bring a resemblance between human traditional medicine and veterinary medicine
Keywords: Intestinal parasitosis; Indigenous knowledge; Medicinal plants; Ethnobotanical survey; Benin